The Income Distribution as a Pure Public Good: A Response - Thurow, Lester C. (Quarterly Journal of Economics, 1973)
I. Brown, Fane, and Medoff, 316. — II. Canterbery and Tuckman, 317. — III. Hochman, Rodgers, and Tullock, 318.